Physiological responses on the Concept II BikeErg and Concept II RowErg in well-trained male rowers - Turner, K. J.; Rice, A. J. (International Journal of Sports Science & Coaching, 2021)
Stationary cycling is a common training mode of rowers, used to provide variety in training programs and prevent overuse injuries commonly associated with the repetitive nature of the rowing stroke. The purpose of this study was to investigate the differences in physiological responses on a Concept II BikeErg (Concept II BikeErg; Concept2 Inc., US) and Concept II RowErg (Concept II Model D; Concept2 Inc., US) at matched submaximal workloads so training load can be appropriately prescribed for stationary cycling. Ten well-trained, male rowers completed 6 min of exercise at four submaximal workloads (50%, 62.5%, 75% and 87.5% of their most recent 2000 m RowErg score) interspersed with 2-minute recovery periods on both ergometers in a single day. Ergometer order was randomised and balanced between groups. At matched power output (PO) results while on the RowErg were significantly higher across all workloads for rate of oxygen consumption (V?O2), rate of carbon dioxide production (V?CO2), minute ventilation (V?E) and heart rate (HR) (p < 0.05) and across the final two workloads for Rating of Perceived Exertion (RPE) and blood lactate concentration (BLa) (p < 0.05). When oxygen uptake at a fixed value (V?O2 = 3.5 L.min-1) was matched between groups results while on the RowErg were significantly lower for PO, BLa, V?CO2, RER and RPE whereas V?E and HR were similar to the BikeErg. These results support the understanding that displayed power output on the RowErg does not account for all work done during the rowing stroke cycle, specifically during the recovery phase. In conclusion, the physiological responses on the Concept II BikeErg are no more closely aligned to the Concept II RowErg than previously shown for similar cycle ergometers from different manufacturers. Due to the lack of consistency between Concept II BikeErg and Concept II RowErg PO, HR is better suited for the prescription of training loads on the BikeErg.